Bubble behavior in horizontal two-phase flow under flow rate fluctuation - Jun-ichi TAKANO (The Japan Society of Mechanical Engineers, 2014)
The study is one on the series of the study on two-phase flow under earthquake, in which the two-phase flow behavior under the seismic vibration is systematically investigated by using both an experimental method and a numerical situation. The present study focuses on a bubbly flow behavior in a horizontal pipe under flow rate fluctuations. The periodical flow rate fluctuation was added to the bubbly or plug flow in a horizontal pipe, and the flow behavior was mainly measured by using image processing and PIV (particle image velocimetry). In the result of the image processing, the characteristic bubble deformation near the pipe wall was observed and the bubble deformation was synchronized with the flow rate fluctuation. The velocity field obtained by PIV showed the characteristic shear flow under the deformed bubble. The motion of both the liquid and the bubble responded to the pressure gradient fluctuation under the flow rate fluctuation, but the response of the bubble motion to the pressure gradient was slightly faster than that of the liquid motion. It indicated that the relative velocity between the bubble and the liquid changed with time. Therefore, the shear flow under the bubble was caused by the relative velocity between the bubble and the liquid, and the bubble was deformed by the shear flow due to the flow rate fluctuation. The numerical simulation code for the gas-liquid two-phase flow with an advanced interface tracking method, TPFIT, also showed the same mechanism of the bubble deformation, i.e., the shear flow under the bubble caused by the flow rate fluctuation.